Pengembangan Model Inquiry Terpadu dengan Strategi SQ3R untuk Meningkatkan Kompetensi Membaca Pemahaman di Sekolah Dasar - Siti Khalimatul Aminah; Fathurohman, Irfai; Sri Surachmi (JURNAL ILMU PENDIDIKAN, 2025)
This research aims to develop an Integrated Inquiry Model with the SQ3R Strategy to improve the reading comprehension skills of elementary school students. The background of this research stems from the low ability of fifth-grade students to understand informative and narrative texts, characterised by difficulties in finding main ideas, identifying detailed information, and drawing conclusions. The research was conducted in three elementary schools in Jepara Regency, namely Rogomulyo 01 State Elementary School, Rogomulyo 02 State Elementary School, and Boloagung 02 State Elementary School, involving fourth-grade students through a research and development (R&D) approach that adapted the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). At the analysis stage, reading learning needs are mapped out through observation, teacher interviews, and analysis of learning outcomes. The design and development phase resulted in an inquiry-based learning model integrated with the SQ3R steps (Survey, Question, Read, Recite, Review), accompanied by learning materials and evaluation instruments validated by content experts and learning experts. Implementation was carried out through limited trials and extensive testing in all three schools, followed by formative and summative evaluations to ensure the model's applicability. The research results show that the developed model is able to significantly improve students' reading comprehension skills. Improvements were seen in the ability to identify main ideas, understand inter-sentence relationships, interpret implied meaning, and reflect on the reading content. Statistical analysis shows a significant difference in scores between pre-tests and post-tests, while qualitative data indicates an increase in students' motivation, learning activity, and metacognitive strategies during the learning process. Overall, this study concludes that the integrated inquiry model with the SQ3R strategy is effective for reading instruction in elementary schools and has the potential to be an alternative pedagogical strategy for improving reading literacy. This model is relevant for wider application as a good practice for reasoning-based learning, exploration, and strengthening the ability to understand text holistically.